The bitter and sweet of chocolate in Europe - Martin, Carla; Sampeck, Kathryn (Socio.hu Társadalomtudományi Szemle, 2015)
This paper examines the changing role of chocolate in European society, especially in light of the food movement turn to slow, small batch, craft chocolate, as a way to critically analyze relationships of labor and race, gender, and class inequality. The changing culture of chocolate consumption over centuries, from its pre–Columbian origins to the ways European colonists culturally and economically adopted chocolate shows a trajectory of increasing permeation of European foods (more foods contain chocolate) and regionalization of tastes in chocolate recipes, most recently by small batch chocolate makers whose work crafts local identity through branding of a tropical product. Europe is the world’s biggest importer and processor of cacao as well as the largest per capita consumer of chocolate. Industrial chocolate is higher in sugar and less complex in taste compared to the variety of local chocolate makers, so chocolate occupies an uneasy place in European diets, especially in light of growing rates of obesity and recent “junk food taxes” that target sugary foods. The historical context and analysis of labor in cacao farming and chocolate production shows a critical reliance on coerced labor. While the legacy of the past has been the decoupling of horrific coerced labor in cacao production from the consciousness of everyday chocolate consumers, the growing vitality of small batch chocolate makers refocuses attention on the country of origin––the conditions of production––as well as local, European tastes–– the conditions of consumption. The authors employ interdisciplinary methodologies of close readings of primary sources that include historical recipes, critical analysis of representation in historic and contemporary images and media, and descriptive economic data of export and consumption levels. This systematic study of taste in chocolate and its social, economic, political, and cultural implications is carried out in an analytical framework of the historical contingency of the social construction of realms of value, and that such construction takes place within global and local political economic forces that tend to propagate inequality as a solution to greater economic efficiency. Examining food access and food justice in the light of ways people produce and consume chocolate can challenge assumptions about social inequalities, race, health, and identity and offer insights into long–term sustainability. The critical analysis of these social factors suggests directions for future education, investment, and action by the fine and craft chocolate industry in Europe that can promote mutual benefits for producers and consumers. Keywords: chocolate, ethics, quality, flavor, anthropology, craft, taste, labor